African agriculture: past performance, future imperatives - Haggblade, Steven; Hazell, Peter B. R.; Kirsten, Ingrid; Mkandawire, Richard (International Food Policy Research Institute, 2004)
African farmers and agricultural policymakers have achieved a series of significant successes in agricultural development, although these successes are still inadequate in number and scale to counter Sub-Saharan Africa's daunting demographic challenge.....What common ingredients and processes underlie these earlier successes? How can policymakers translate these lessons into improved performance going forward? By examining instances in which important advances have occurred in the past in African agriculture, IFPRI, NEPAD, and colleagues aim to identify promising avenues for achieving similar success in the future. The following briefs offer highlights of some of these important accomplishments and lessons learned from past successes in African agriculture. Collectively, they aim to identify key ingredients necessary for building on these individual cases and expanding them into broad-based agricultural growth.